2010
DOI: 10.1186/1744-859x-9-14
|View full text |Cite
|
Sign up to set email alerts
|

The emerging modern face of mood disorders: a didactic editorial with a detailed presentation of data and definitions

Abstract: The present work represents a detailed description of our current understanding and knowledge of the epidemiology, etiopathogenesis and clinical manifestations of mood disorders, their comorbidity and overlap, and the effect of variables such as gender and age. This review article is largely based on the 'Mood disorders' chapter of the Wikibooks Textbook of Psychiatry http://en.wikibooks.org/wiki/Textbook_of_Psychiatry/Mood_Disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 227 publications
0
13
0
2
Order By: Relevance
“…Emotional reactivity/lability (increased) "Unstable and rapidly changing emotions due to hyper-reactivity to emotional stimuli" (Fountoulakis, 2010). Socio-emotional stimuli Emotional faces, voices, or images.…”
Section: Emotion Regulationmentioning
confidence: 99%
“…Emotional reactivity/lability (increased) "Unstable and rapidly changing emotions due to hyper-reactivity to emotional stimuli" (Fountoulakis, 2010). Socio-emotional stimuli Emotional faces, voices, or images.…”
Section: Emotion Regulationmentioning
confidence: 99%
“…Bipolar disorder (BD) and major depressive disorder (MDD) are severe mood disorders often characterized by a perseverative course across the affected individuals' lifetimes (Fountoulakis, 2010;Grande, Berk, Birmaher, & Vieta, 2016;Hardeveld, Spijker, De Graaf, Nolen, & Beekman, 2010;Kessler et al, 2003). Often enough, it is most difficult to distinguish patients with BD and MDD as both disorders manifest themselves highly similar in depressive episodes.…”
Section: Introductionmentioning
confidence: 99%
“…Although originally it has been suggested that the prevalence of manic depressive psychosis was approximately 1%, nowadays we are aware that the actual prevalence of the disorder depends on the definition 6 . Bipolar disorder type I (BD-I) and type II (BD-II) are both disabling conditions and show a combined prevalence rate of 3.7% 7,8 .…”
Section: Introductionmentioning
confidence: 99%
“…Recent international research results indicate that DSM-defined mixed episodes (including simultaneous manifestation of full blown mania and depression) are rather the exceptions than the rule 1 . Instead, there is usually a combination of manic and depressive symptoms in a clinical manifestation which does not meet the DSM criteria of manic, depressive or mixed episodes, leaving Not-Otherwise-Specified (NOS) mood episode as the only possible diagnosis 6 , which is a clinical picture manifesting with a simultaneous presence of symptoms of depression and mania, and exhibiting a fluctuating course 14,15 . Manic and especially hypomanic symptoms often remain unrecognised because the mood is irritable instead of hyperthymic.…”
Section: Introductionmentioning
confidence: 99%